Integrating multiphasic CuSx/FeSx nanostructured electrocatalyst for enhanced oxygen and hydrogen evolution reactions in saline water splitting - Mottakin M.; Sukor Su'ait M.; Selvanathan V.; Ibrahim M.A.; Abdullah H.; Akhtaruzzaman M. (Elsevier Ltd, 2025)
This study employed an electrodeposition approach to synthesize multiphasic CuSx and FeSx on nickel foam (NF) for application in saline water splitting. This multiphasic electrocatalyst exhibits a cauliflower morphology and develops a porous fused-type morphology upon partial oxidation. The NF/CuSx/FeSx electrode with partial oxidation exhibits the lowest overpotential of 181 mV at 10 mA/cm2 and a Tafel slope of 163 mV/decade for the oxygen evolution reaction (OER). The overpotential of 73 mV at 10 mA/cm2 and a Tafel slope of 165 mV/decade were found for the hydrogen evolution reaction (HER). A charge transfer coefficient value of ?0.5 in OER and HER indicates that the rate-determining step depends on the surface adsorption of reaction species. The presence of an unpaired electron during partial oxidation can create additional active sites and reduce solution resistance (Rs). This can improve the interaction between reactants and intermediates, improving OER and HER performance. NF/CuSx/FeSx composites demonstrated robust stability using real seawater splitting over 80 hours in HER with negligible degradation. However, catalyst breakdown in OER after 10 hours due to prolonged exposure to higher potentials, resulting in oxidative corrosion. This study offers a multiphasic electrode design using the electrodeposition technique to produce green hydrogen energy through seawater splitting. ? 2024 Elsevier B.V.